A novel control strategy for the multi-step straightening process of long/extra-long linear guideways. (May 2019) - Zhang, Yongquan; Lu, Hong; Zhang, Xinbao; Ling, He; Fan, Wei; Wei, Qinyu; Lian, Yang
The straightening process for a linear guideway with particular cross-section shape is normally conducted by the three-point pressure bending method. However, the single-step straightening process (SSSP) of a long/extra-long linear guideway may make the workpiece from a single-curvature curve into a more complex shape. Due to these limitations of SSSP, a quantitative control strategy for the multi-step straightening process (MSSP) of a long/extra-long linear guideway is proposed in this paper based on the straightening principle of SSSP. Firstly, the predictive models for straightening stroke and helix angle after unloading with respect to SSSP are developed based on the elasto-plastic theory and curvature integral model. Depending on the established analytical model for SSSP, the MSSP is then mathematically modelled to obtain corresponding straightening parameters considering feeding process, clamping process and straightening process. Besides, the finite element method has been applied to validate the developed mathematical model for the MSSP. Taking the approach of a linear guideway as an example, the experimental results have also shown that the proposed control strategy is appropriate for the MSSP of a long/extra-long linear guideway.